Role of bronchoalveolar lavage in the diagnosis of lung cancer - Sarkar, Shish Mohammad; Khatun, Julekha; Hossain, A. K. M. Mosharraf; Rahman, Mohammad Atiqur; Ahmed, Shamim; Chakrabortty, Rajashish (International Journal of Research in Medical Sciences, 2022)
Background: Early diagnosis of lung cancer plays a vital role in reducing the lung cancer death rate. Different modalities can be applied e.g. radiology, bronchoscopy, bronchoalveolar lavage (BAL), and fine needle aspiration cytology. Cytological diagnostic techniques are safer, economical, and provide quick results. The aim of the study was to find out diagnostic yields of bronchoalveolar lavage in diagnosing lung cancer, and to determine the sensitivity, and specificity of BAL fluid cytology considering the bronchial biopsy as the gold standard. Methods: This cross-sectional study was carried out in the Department of Respiratory Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka during the period from November 2018 to March 2020 with a total of 38 participants. Results: 33 (86.84%) patients were male, and 5 (13.16%) were female; the mean age was 58.29±13.11 years. In clinical presentations, cough was present in all 100% of the patients, and some more frequent presentations were shortness of breath in 26 (68.4%), hemoptysis in 24 (63.15%), and chest pain in 21 (55.26%). Majority of the patients (78.95%) were smokers. Considering histopathological findings, maximum patients had squamous cell carcinoma 13 (38.23%), then adenocarcinoma 11 (32.35%), small cell carcinoma 5 (14.70%), large cell carcinoma 3 (8.82%), and poorly differentiated non-small cell carcinoma 2 (5.88%). The sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy of BAL were 70.59%, 100%, 100%, 28.57%, and 73.68% respectively. Conclusions: BAL fluid cytology is a useful tool for the diagnosis of lung cancer. It has good sensitivity, and specificity, and shows nearly identical information as biopsy.